2021
DOI: 10.1007/s00192-021-04907-7
|View full text |Cite
|
Sign up to set email alerts
|

Colpocleisis as an obliterative surgery for pelvic organ prolapse: is it still a viable option in the twenty-first century? Narrative review

Abstract: Introduction and hypothesis The aims were to review the literature from the last two decades and analyze treatment efficacy and findings of the studies on colpocleisis. Methods A systematic search was conducted within the MEDLINE/PubMed and ClinicalTrials.gov databases, using the following keywords: pelvic organ prolapse (POP), colpocleisis, obliterative, and LeFort. All English full-text prospective and retrospective observational and interventional studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 53 publications
(269 reference statements)
2
15
0
Order By: Relevance
“…The high success rate, patient satisfaction and low regret rate reported in the literature (1,(7)(8)(9) were supported by this study. With a mean follow-up of 49.6 months, there were two (2.2%) recurrent cases.…”
Section: Discussionsupporting
confidence: 84%
“…The high success rate, patient satisfaction and low regret rate reported in the literature (1,(7)(8)(9) were supported by this study. With a mean follow-up of 49.6 months, there were two (2.2%) recurrent cases.…”
Section: Discussionsupporting
confidence: 84%
“…The study found that 48 female patients underwent colpocleisis due to POP. The mean age of these patients was 73.25±5.45 (60-80), gravidity was 4.58±2.38 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), and parity was 4.08±1.45 (2)(3)(4)(5)(6)(7). Twenty-eight of the patients (58.3%) underwent partial colpocleisis (LeFort).…”
Section: Resultsmentioning
confidence: 99%
“…Protrusion of pelvic organs (uterus, rectum, bladder) toward or out of the vagina is called pelvic organ prolapse (POP). The main purpose of treatment POP is to improve symptoms, and reconstructive or obliterative surgical approaches are available (1,2). The treatment approach depends on the patient's expectations and preferences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations